Human Security, Gender and Development: A Test-Case for Iceland’s Assistance Policy - Nanna Rún Ásgeirsdóttir 1981- (2010)
Ritgerðin er lokuð fram í janúar 2011. The aim of this thesis is to seek an understanding of women’s human security in developing countries, and to ask whether the human security concept as such can live up to expectations as a practical guide to improving women’s lot. Iceland’s stance on aid provision and its promotion of gender issues is also examined, to see whether the country’s efforts are being directed to the right targets and for maximum effect. The subject is approached by introducing a historical summary of the rise of ‘human security’ thinking followed by a theoretical discussion of the concept. This twofold introduction provides a clearer picture of the concept’s utility and its limitations. To see how different security threats may face women within developing countries, the seven categories of human security defined in the 1994 UNDP report are then used to give a non-exhaustive review of the problems. This approach is then narrowed down to focus on Uganda as a test case. The results show that there can be no human security without including the dimension of gender, as gender equality is a precondition for human security. The review also highlights that despite the concept’s limits for framing practical policies, it does help in asking important questions. Finally Iceland’s international development efforts are shown to have increased considerably in recent years with many important steps taken to this end. In the same manner Iceland is shown to have increased its emphasis on issues of gender equality and women’s security, despite still having much to learn in this and other aspects of aid. Many hopeful prospects are in sight for Iceland in future: as a donor, a partner, and in terms of mutual learning about the true inter-linkages of gender, security and development. Varnarmálastofnun, Alþjóðamálastofnun